COMPARATIVE STUDY ONMANUFACTURING PROCESSES OFA SWIRLER CASING - MdYunus, Ahmad Faiz (Universiti Teknologi Petronas, 2013)
Process planning is a systematic method to determine the engineering processes and systems to manufacture a product competitively and economically. In this project, the process plan is subjected to analysis for fabrication process of swirler by machining and casting. The scope of study covered process sequence, machine tools and fixtures. The comparative study of fabrication swirler casing will be based on the analysis from machining and casting process plan that include the process time and cost consumption. Most of data for this study were obtained from literatures and experiments. The total process cost by casting is lower than machining process with RM 10113 for casting and RM 12578 for machining. However, total estimated process time for casting higher than machining which are 151 hr and 139.6 hr respectively. These findings have significant implications for the commercial application of manufacturing processes.